2009
DOI: 10.1016/j.jacc.2009.03.016
|View full text |Cite|
|
Sign up to set email alerts
|

Contrast-Enhanced Whole-Heart Coronary Magnetic Resonance Angiography at 3.0-T

Abstract: OBJECTIVES The purpose of this study was to prospectively evaluate the diagnostic performance of 3.0T contrast-enhanced whole-heart coronary magnetic resonance angiography (CMRA) in patients with suspected coronary artery disease. BACKGROUND A slow-infusion, contrast-enhanced whole-heart CMRA approach has recently been developed at 3.0T. The accuracy of such technique has not yet been determined among patients with suspected coronary artery disease. METHODS 3.0T contrast-enhanced whole-heart CMRA was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(98 citation statements)
references
References 24 publications
2
96
0
Order By: Relevance
“…Assessable segments had image quality of ≥ 2, 9,12) and estimated assessable proximal segments were segments 1, 2, 3, 5, 6, and 11, and had an image quality of ≥ 2. Statistical analysis: Data are reported as the mean ± standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…Assessable segments had image quality of ≥ 2, 9,12) and estimated assessable proximal segments were segments 1, 2, 3, 5, 6, and 11, and had an image quality of ≥ 2. Statistical analysis: Data are reported as the mean ± standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, magnetic resonance imaging (MRI) and CT have emerged as the most promising non‐invasive imaging techniques in the primary diagnosis of CAD and HF. While a meta‐analysis published in 2010 suggested that CT was superior to MRI, recent studies directly comparing CT and MRI or X‐ray coronary angiography and MRI indicated that there was no significant difference when assessing presence or absence of >50% coronary artery stenosis 19, 20, 21, 22. For the visualization of myocardial ischaemia in HF, CMR was demonstrated to be superior to single‐photon emission CT in a large prospective trial with 752 recruited patients 9.…”
Section: Numbersmentioning
confidence: 99%
“…High-field-strength 3.0-T systems improve the signal-to-noise ratio of coronary MR angiography, such that diagnostic accuracy of 3.0-T contrast-enhanced imaging approaches that of some coronary CTA systems (35). However administration of contrast is not without risks, such as the potential for nephrogenic systemic fibrosis in patients with severe renal dysfunction who receive gadolinium agents, resulting in a recent FDA advisory.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%